Reflections on Foucault's concept of critical ontology - Erozan, Bo?aç (Bogazici Universitesi, 2006)
The article concentrates on Michel Foucault's concept of critical ontology. The emphasis is on the demonstration of the theoretical viability of the concept by way of questions posed by Martin Heidegger and Hannah Arendt. As a "philosophical ethos" and a "philosophical attitude," critical ontology is explored with regard to the Heideggerian conception of thinking and being in the world. As a philosophical life, in turn, critical ontology is subjected to a discussion that revolves around Arendt's arguments on the predicament of the philosopher in the realm of human affairs. The article concludes that critical ontology is beyond a Heideggerian orientation toward "meditative thinking" just as it is beyond the Arendtian problem of truth in the public realm.
Keywords: critical analysis; philosophy